مفتشية العمل كوسيط بين العامل و رب العمل - عمارة, تواتية (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
هدفت هذه الدراسة إلى تثمين من جانب سوسيولوجي دور الوساطة التي تتبناها مفتشية العمل في فض نزاعات العمل، خاصة تلك المتعلقة بحوادث العمل، وذلك من خلال دراسة ميدانية في مفتشية العمل بولاية مستغانم. قمنا في هذا السياق بتحليل المعطيات المتاحة في ملفات الشكاوى المقدمة خلال سنة 2023 والبالغ عددها 32 ملفًا. كما شاركنا في 8 جلسات مصالحة كطراف ملاحظ ، مما سمح لنا بتسجيل العديد من الملاحظات والاستنتاجات التي كانت مكملة لما توصلنا اليه في تحليل الملفات , بالاضافة الى هذا أجرينا مجموعة من المقابلات مع إطارات المفتشية . من بين أهم النتائج التي توصلنا إليها في هذه الدراسة ، تأكيد الفرضيات التي صيغت في الإشكالية وتبين محدودية دور مفتشية العمل كوسيط بين العامل وصاحب العمل في حل نزاعات العمل، وإحالة معظم القضايا إلى المحكمة للنظر و الفصل فيها .
دراسة على عينة من العمال المصابين بحادث عمل بمفتشية العمل لولاية مستغانم
This study aimed to sociologically assess the role of mediation adopted by the labor inspectorate in resolving workplace disputes, especially those related to work accidents, through a field study in the labor inspectorate of Mostaganem province. In this context, we analyzed the available data from complaint files submitted during the year 2023, totaling 32 files. Additionally, we participated in 8 conciliation sessions as observers, allowing us to record numerous observations and conclusions complementing our analysis of the files. Furthermore, we conducted a series of interviews with the labor inspectorate's officials. Among the key findings of this study was the confirmation of the hypotheses formulated in the problem statement, revealing the limited role of the labor inspectorate as a mediator between the worker and the employer in resolving labor disputes, with most cases being referred to the court for resolution.
Keywords: مفتشية العمل , العمل , حوادث العمل , العمل , المصالحة , الوساطة , نزاعات العمل ، الصراع , النقابة .; labor inspectorate, work, work accidents, reconciliation, mediation, labor disputes, conflict ,union